"The Sort of War They Deserve"? The Ethics of Emerging Air Power and the Debate over Warbots. Issue 2 (3rd July 2018) - Banta, Benjamin R.
ABSTRACT: As new military technologies change the character of war by empowering agents in new ways, it can become more difficult for our ethics of war to achieve the right balance between moral principle and necessity. Indeed, there is an ever-growing literature that seeks to apply, defend and / or update the ethics of war in light of what is often claimed to be an unprecedented period of rapid advancement in military robotics, or warbots. To increase confidence that our approach to this development finds success in appropriately constraining war, this article compares our current discourse to the ethical debate over the rise of air power during the interwar period. As moral norms largely failed to constrain air power in World War II, by highlighting the interrelated processes of technological change, ethical debate, and the eventual reconciliation of war practice and war ethics, this historical case offers insights that can help military ethicists maintain their "critical edge" as remote and autonomous robotic weapons continue to mature and proliferate.